2020
DOI: 10.1108/ijbm-05-2019-0191
|View full text |Cite
|
Sign up to set email alerts
|

A transaction cost explanation of the card-or-cash decision among Vietnamese debit card holders

Abstract: PurposeThis research provides a new perspective in explaining cardholders' willingness to use debit cards instead of cash by applying the transaction costs economic theory. This study also expands the adaptation of transaction cost economics theory in explaining consumer behaviour by investigating the moderating effects of income and education level on the relationship between perceived transaction costs and willingness to use debit cards.Design/methodology/approachThe conceptual framework was developed primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…This leads customers to prefer the e-payment option compared to COD, as the benefits of this method are enhanced by the avoidance of extra fees pertaining to each provider. This idea is in accordance with findings of Hoang and Vu (2020) who supported the theory of transaction cost economics as an explanation of the intention to use debit cards. They found that the perception of adaptation costs mediated the relationship between uncertainty and intention to use this type of e-payment.…”
Section: Results Analysis and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This leads customers to prefer the e-payment option compared to COD, as the benefits of this method are enhanced by the avoidance of extra fees pertaining to each provider. This idea is in accordance with findings of Hoang and Vu (2020) who supported the theory of transaction cost economics as an explanation of the intention to use debit cards. They found that the perception of adaptation costs mediated the relationship between uncertainty and intention to use this type of e-payment.…”
Section: Results Analysis and Discussionsupporting
confidence: 92%
“…Indeed, by paying online, customers will avoid the fees of COD payment. This is similar to the main assumptions of the theory of transaction cost economies which highlight the fact that consumers choose a payment method which reduces transaction costs (Hoang and Vu, 2020). Indeed, most of the e-retailing companies charge a COD fee for each provider who sells online with the e-shopping platform, whereas the e-payment method incurs no transaction fees for the website.…”
Section: Results Analysis and Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Despite the growing number of research on retail payments, due to the limited data on individual payment transactions, explaining the real drivers of consumer payment behaviour remains not an easy task. Most research discusses how consumers pay (Kennickell & Kwast, 1997;Humphrey et al, 2001;Hayashi & Klee, 2003;Bounie & Francois, 2006;Klee, 2006Klee, , 2008De Grauwee et al, 2006;Chen, 2008;Pousttchi, 2008;Carlos & Taylor, 2009;Zinman, 2009;Schierz et al, 2010;Kosse, 2013;Shaw, 2014;Hoang & Vu, 2020;Karjaluoto et al, 2020;Raman & Aashish, 2020), and only a few try to find the answer to the question of why. Even less, try to find what should be done to motivate consumers to switch from cash to other non-cash payment methods.…”
Section: Introductionmentioning
confidence: 99%